Penguatan Pengetahuan Remaja Melalui Edukasi Risiko Dan Dampak Kehamilan Usia Dini Di SMAN 1 Kapontori, Desa Mabulugo, Kecamatan Kapontori - Hafirah Hafirah; Oca Oca; Veland Eveliyn Veronika; Hesni Hesni; Muh. Subhan Ramadhan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Early pregnancy among adolescents remains a significant public health issue because it can negatively affect physical, psychological, social, and educational aspects of adolescents’ lives. Limited knowledge regarding the risks and impacts of early pregnancy is one of the contributing factors to the increasing incidence of adolescent pregnancy. This study aimed to determine the level of knowledge among senior high school students regarding the risks and impacts of early pregnancy in Desa Mabulugo. The study used a descriptive quantitative design with a cross-sectional approach. Data were collected through the distribution of questionnaires to 48 senior high school students selected using total sampling techniques. The results showed that 62.5% of respondents had a moderate level of knowledge regarding the risks and impacts of early pregnancy, 25% had good knowledge, and 12.5% had low knowledge. Several students were still found to have misconceptions regarding reproductive health complications, psychosocial consequences, and the ideal age for pregnancy. The findings indicate the importance of continuous reproductive health education through schools, families, and community-based health programs. Improving adolescent knowledge is expected to reduce the risk of early pregnancy and encourage healthier attitudes and behaviors among students.